Wild dark shore : a novel [compact disc, unabridged] - McConaghy, Charlotte (Macmillan Audio, 2025)
Dominic Salt and his three children are caretakers of Shearwater, a tiny island not far from Antarctica. Home to the world's largest seed bank, Shearwater was once full of researchers. But with sea levels rising, the Salts are now its final inhabitants, packing up the seeds before they are transported to safer ground. Despite the wild beauty, isolation has taken its toll on the Salts. Raff, eighteen and suffering his first heartbreak, can only find relief at his punching bag; Fen, seventeen, has started spending her nights on the beach among the seals; nine-year-old Orly, obsessed with botany, fears the loss of his beloved natural world; and Dominic can't stop turning back toward the past, and the loss that drove the family to Shearwater in the first place. Then, during the worst storm the island has ever seen, a woman washes up on shore. As the Salts nurse the woman, Rowan, back to life, their suspicion gives way to affection, and they finally begin to feel like a family again. Rowan, long accustomed to protecting her heart, begins to fall for the Salts, too. But Rowan isn't telling the whole truth about why she set out for Shearwater. And when she discovers the sabotaged radios and a freshly dug grave, she realizes Dominic is keeping his own dark secrets. As the storms on Shearwater gather force, can they trust each other enough to protect one another, and the precious seeds in their care? And can they finally put the tragedies of the past behind them to create something new, together?